Gastroliths associated with a juvenile elasmosaur (Plesiosauria, Elasmosauridae) from the Snow Hill Island Formation (upper Campanian-lower Maastrichtian), Vega Island, Antarctica - O'gorman, Jose Patricio; Olivero, Eduardo Bernardo; Cabrera, Daniel Alfredo (Alcheringa: An Australasian Journal of Palaeontology)
Gastroliths associated with a juvenile elasmosaur (Plesiosauria, Elasmosauridae) from the Snow Hill Island Formation (upper Campanian-lower Maastrichtian), Vega Island, Antarctica. Alcheringa 36, 531-541. ISSN 0311-5518.One of the unresolved problems concerning the palaeobiology of plesiosaurs is the function of gastroliths. A new juvenile specimen referred to Elasmosauridae indet., collected from the Cape Lamb Member of the Snow Hill Island Formation (upper Campanian-lower Maastrichtian) from Cape Lamb, Vega Island, Antarctic Peninsula with gastroliths, provides the opportunity to add information about this issue. The specimen consists of approximately 20% of a partially articulated skeleton including 333 gastroliths. Taphonomic evidence indicates rapid burial and possibly different taphonomic pathways for the dorsal (articulated) and caudal (disarticulated) regions. Analysis of the 333 gastroliths determined the mean major axis to be 14.32 mm, the mean maximum projection sphericity to be 0.7 and the standard deviation to be 1.1. Following Krumbein classification, most of the gastroliths are disk-shaped (35.4%), spheroid (34%) and cylindrical (21.3%). According to Powers's categories, most of the gastroliths are rounded (71.2%). Petrographically, the gastroliths that are larger than 15 mm (major axis) are mostly volcanic rhyolites (78.3%) and fine-grained quartz aggregates (11.6%); together with minor granitic rocks (3.1%), mudstones (3.1%) and aphanitic volcanics (3.9%); similar percentages were present among the smaller clasts. The acidic volcanic clasts likely derive from the volcanic Antarctic Peninsula Group (GPVA; Middle-Upper Jurassic). The mean values for sphericity and oblate-prolate index (OP index) indicate a fluvial origin for the gastroliths. The method of estimation of the maximum prey-size using gastroliths is discussed. The available data provides evidence against the hydrostatic function of the gastroliths because the total weight of the gastroliths is insufficient to modify the hydrostatic ...